Endocytic events in TCR signaling: focus on adapters in microclusters - Balagopalan, Lakshmi (2009)
Although the critical role of T-cell receptor (TCR) microclusters in T-cell activation is now widely accepted, the mechanisms of regulation of these TCR-rich structures, which also contain enzymes, adapters, and effectors, remain poorly defined. Soon after microcluster formation, several signaling proteins rapidly dissociate from the TCR. Recent studies from our laboratory demonstrated that the movement of the adapters linker for activation of T cells (LAT) and Src homology 2 domain-containing leukocyte protein of 76 kDa (SLP-76) away from initial microcluster formation sites represents endocytic events. Ubiquity-lation, Cbl proteins, and multiple endocytic pathways are involved in the internalization events that disassemble signaling microclusters. Several recent studies have indicated that microcluster movement and centralization plays an important role in signal termination. We suggest that microcluster movement is directly linked to endocytic events, thus implicating endocytosis of microclusters as a means to regulate signaling output of the T cell.